The Influence of Ambient Environmental Conditions on the Survival of Salmonella enteric Serovar typhimurium in Poultry Litter - Soliman, Essam S.; Taha, Ensaf G.; Sobieh, M.A.A.; Reddy, P.G. (International Journal of Poultry Science, 2009)
Combined effects of temperature, relative humidity and litter pH in the presence or absence of organic matter on the survival of S. typhimurium over time was studied. The litter (L: 30 cm x W: 25 cm x D: 6 cm aluminum trays filled with wood shavings) was inoculated with S. typhimurium at initial concentration of 4.8 x 107CFU/ml, then litter trays were placed in a room with microclimate similar to that of a naturally ventilated poultry house. The periodical measurement of S. typhimurium population in poultry litter in relation to the ambient environmental conditions revealed that: in the absence of organic matter; there was a non-significant (p